2015
DOI: 10.4239/wjd.v6.i1.192
|View full text |Cite
|
Sign up to set email alerts
|

Literature review of type 2 diabetes mellitus among minority Muslim populations in Israel

Abstract: This review surveys the literature published on the characteristics and implications of pre-diabetes and type 2 diabetes mellitus (T2DM) for the Arab and Bedouin populations of Israel. T2DM is a global health problem. The rapid rise in its prevalence in the Arab and Bedouin populations in Israel is responsible for their lower life expectancy compared to Israeli Jews. The increased prevalence of T2DM corresponds to increased rates of obesity in these populations. A major risk group is adult Arab women aged 55-6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…A review including patients with diabetes of Arab and Bedouin origin in ‘Israel’, yet, also found evidence of high rates of hospitalizations and micro and macrovascular complications. Beyond this, the review stated that financially difficulties are frequently expressed as cause for inadequate healthcare and consequent complications [ 39 ]. Another study stated that high numbers of patients, insufficient staff training, and inadequate infrastructure are the main impediments to the proper management of diabetes in Palestine.…”
Section: Discussionmentioning
confidence: 99%
“…A review including patients with diabetes of Arab and Bedouin origin in ‘Israel’, yet, also found evidence of high rates of hospitalizations and micro and macrovascular complications. Beyond this, the review stated that financially difficulties are frequently expressed as cause for inadequate healthcare and consequent complications [ 39 ]. Another study stated that high numbers of patients, insufficient staff training, and inadequate infrastructure are the main impediments to the proper management of diabetes in Palestine.…”
Section: Discussionmentioning
confidence: 99%
“…This study took a strengths-based approach, using the experience and analysis of community members with diabetes as the starting point both for evaluating healthcare system successes and shortcomings, and for identifying community needs, strengths and solutions. It adds to the body of strengths-based approaches in the literature that serve to counterbalance and critique deficit-based approaches characterizing Indigenous and other marginalized minority patients as "problematic" or "non-compliant" [4,6,39].…”
Section: Discussionmentioning
confidence: 99%
“…Indigenous and other marginalized racial/ethnic minorities have poorer health status than majority populations, including higher rates of type 2 diabetes, and diabetes-related complications and mortality [1][2][3]. In addressing these disparities, healthcare and government policy makers have typically used a deficit-based discourse that frames the problem as a deficiency, lack or failure of the Indigenous/minority population in comparison to a utopian non-Indigenous/majority ideal [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This community is characterized by a high rate of consanguineous marriages with a common founder effect [1617]. Recently, a westernized lifestyle was adopted by most of the Arab population in Israel [18]. It was found that the main causes of death that might contribute to the lower age of Arabs compared to Jews could be due to chronic diseases, especially ischemic heart disease and diabetes [19].…”
Section: Introductionmentioning
confidence: 99%